Comparative possibilities of using limestone "Visočica" and dolomite "Virpazar" as fillers in paper production - Krgović Milun M.; Blagojević Nada Z.; Blagojević Nikola S. (Hemijska Industrija, 2004)
Non-metallic mineral fillers strongly influence the characteristics and quality of paper. "Visočica" limestone and "Virpazar" dolomite were used to prepare paper samples in this study. The characteristics of such paper samples produced on a laboratory paper machine are presented. The used fillers and paper pulp were also characterized. The following paper characteristics were investigated: gramature, thickness, softness, air permeability, resistance to tearing and stretching, paper ash and retention. The experiments were performed in order to compare the influence of the physico-chemical and structural qualities of the examined carbonate type fillers on the paper properties. The results of the investigation indicated the technological reasons for using these non-metallic mineral raw materials as fillers in the paper industry regarding the mechanical paper characteristics, as well as other properties.